Organizational-level analysis of the employees' compensation system in the Republic of Serbia - Gašić Dimitrije; Berber Nemanja; Slavić Agneš (Journal of Engineering Management and Competitiveness, 2023)
The purpose of the research is an analysis of the employee compensation system at the organizational level in the Republic of Serbia to determine the effects of the position of employees in the company, the size of the company, belonging to the private or public sector, headquarters, type, and belonging to the service or manufacturing sector. The sample was collected through an electronic Google Forms questionnaire, where respondents had the opportunity to answer two parts of the questionnaire, the first part related to organizational characteristics and the second part to questions about the assessment of the compensation system. A total of 1121 employees answered the questions, and after collected database performed by the authors, a non-parametric analysis was conducted using the Mann-Whitney and Kruskal Wallis test using the IBM SPSS statistics software program for data processing. The results indicate the existence of statistically significant differences in the level of application of the compensation system at the organizational level in the Republic of Serbia. Due to the insufficient number of papers on this topic, it can be said that this research represents a great contribution, but also a shortcoming due to the impossibility to compare with the author's research on this topic in the Republic of Serbia. The recommendation for future research refers to a larger number of respondents and the possibility of determining the impact on the working attitudes and behaviour of employees.